Prospective study of definitive chemoradiation in locally or regionally advanced squamous cell carcinoma of the skin. Issue 4 (29th December 2016) - Nottage, Michelle K.; Lin, Charles; Hughes, Brett G. M.; Kenny, Lizbeth; Smith, David D.; Houston, Kathleen; Francesconi, Alessandra
ABSTRACT: Background: The purpose of this study was to present our evaluation of the outcomes of concurrent chemoradiotherapy (CRT) in patients with locally advanced cutaneous squamous cell carcinoma (SCC). Methods: This was a prospective phase II study. The primary endpoint was complete response (CR). Patients with locally/regionally advanced cutaneous SCC deemed unsuitable for surgery received definitive radiotherapy (RT; 70 Gy in 35fractions) and concurrent weekly platinum‐based chemotherapy (cisplatin 40 mg/m2 or carboplatin area under the curve 2). Results: Twenty‐one patients were enrolled in this study. Eighteen patients had a locally advanced primary or nodal disease in the head and neck region with 66% having stage IV nonmetastatic disease. Of 19 evaluable patients, 10 achieved a CR to definitive CRT with 2 further patients rendered disease‐free by salvage surgery for an overall CR of 63%. Conclusion: This is the only prospective series of CRT for cutaneous SCC. A high CR rate was documented in patients with locoregional advanced disease who were unable to undergo surgery. © 2016 Wiley Periodicals, Inc. Head Neck 39: 679–683, 2017